Determinants of United States’ Vertical and Horizontal Intra-Industry Trade - Thorpe, Michael; Leitao, Nuno (Walter de Gruyter GmbH, 2013)
This paper investigates bilateral intra-industry trade between the United States and its major trading partners over the period 1995–2008. Intra-industry trade (IIT) is decomposed into horizontal (HIIT) and vertical (VIIT) components. HIIT dominates the total two-way trade of the United States andits share relative to VIIT has been rising over time, particularly with neighbouring trade partners and with China. Using pooled panel data, country-level determinants of IIT, HIIT and VIIT are investigated. The results, overall, tend to conform with a priori expectations and provide empirical support for anumber of propositions suggested by theory. Findings indicate that the relative similarity of the economies of trading partners, their geographical proximity, FDI and overall market size are important influences on bilateral HIIT flows for the United States. VIIT, on the other hand, is found to be driven in large part by economic differences between partners as well as the market size and closenessof trading partners.